Peran Spiritual dan Etika Perempuan dalam Karya Al-Ghazali: Implikasi untuk Pendidikan Gender - Putri Humaira Djufri; Mustamin Giling (Al-Kindi, 2026)
This research explores the relationship between women's ethics in Al-Ghazali's thought and gender education in the contemporary Muslim world. Al-Ghazali, a prominent 11th-century Islamic scholar, emphasized the importance of spirituality and morality in daily life, including in the context of women. Through qualitative research using literature review methods, this study analyzes Al-Ghazali's works, particularly "Ihya Ulum al-Din," to identify ways in which his proposed spiritual values can be applied in educational curricula to support gender equality. The findings reveal that Al-Ghazali acknowledges women's equal rights and responsibilities in pursuing knowledge and spiritual development, positioning women not merely as domestic subjects but as autonomous spiritual beings. His concept of justice ('adalah) demands full recognition of equal dignity for all humans, regardless of gender. This research demonstrates that integrating Al-Ghazali's spiritual and ethical values into gender education curricula can create more inclusive learning environments, overcome gender stereotypes, and promote women's active participation in various aspects of life. Despite implementation challenges such as gender stereotypes and cultural norms, significant opportunities exist to advance gender education in the Muslim world through Al-Ghazali's progressive perspectives on women's roles in society.